Getting On: Ageing, mess and the NHS. Issue 2 (July 2016) - Johnson, Beth
This article examines the feminist foundations, style and performances of key writer-stars Jo Brand, Vicki Pepperdine and Joanna Scanlan in the British Broadcasting Corporation sitcom Getting On (2009–2012). Paying close attention to the 'life experience' of these women, it aims to think through the multiple, acute politics of representation that the show offers up, suggesting that sex, class and age operate as key emotional loadstones. Examining the hierarchical interactions between medical staff, this article also argues that the minutiae of social exchanges made visible in the sitcom reveal the sickness of the National Health Service to be connected to new managerialism and male privilege.